Vegetation survey at West Avon Preserve in 2025 - Monahan, Robert C., author; Smith, Jessica P., author; Colorado Natural Heritage Program, publisher (Colorado State University. Libraries, 2026)
The Colorado Natural Heritage Program (CNHP) in conjunction with Eagle Valley Land Trust has set out to better understand the vegetation present and assess the Harrington's beardtongue (Penstemon harringtonii) population at the West Avon Preserve. In June of 2025 CNHP botanists established four 50-meter-long vegetation monitoring transects within four study areas at the West Avon Preserve. Two transects two were established within a planned treatment area, one was established in a non-treatment (control) area, and one was established in an area that may or may not receive future treatment. Additionally, Harrington's beardtongue was surveyed for within the treatment and control areas. Thirty-eight vascular plant species and one moss were found along the transects. Thirty-six of which were native plants species and two are introduced species. The mean conservation value (C-value) of the of the plants species found was 5.25, and the Floristic Quality Index (FQI) across all the transects is 31.5. Harrington's beardtongue was found at 19 new points and a total of 40 individuals were found. Follow-up monitoring of the transects post-treatment are required to understand the effects of treatments on the vegetation.
Vegetation survey at West Avon Preserve, 2025
Report prepared for: Eagle Valley Land Trust.
Locations of rare plants have been redacted from this document.
Keywords: ecology; vegetation mapping and classification